PENGARUH PENERAPAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN MINAT BELAJAR SISWA DALAM PEMBELAJARAN SENI BUDAYA KELAS IV SD NEGERI 1 SUKAMANAH - Nursakinah, Tsani; Syarif Hidayat, Ujang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the application of audiovisual media on students' learning interest in learning Arts and Culture of grade IV of SD Negeri 1 Sukamanah. This study is motivated by the low interest in learning students caused by the less than optimal use of learning media, where teachers still predominantly use lecture methods without the support of interesting media. This study uses a quantitative approach with a pre-experimental design (pre-experimental design) one-group pretest–posttest. The subjects in this study were 41 students. Data collection techniques were carried out through questionnaires, observations, and documentation. The results showed that before the application of audiovisual media, the average pre-test or initial questionnaire of students' learning interest was 52.46. After the application of audiovisual media, the average posttest or final questionnaire value increased to 66.29. The results of the statistical test showed a calculated t value of 11.908 greater than t table 2.021 with a significance value of 0.000 <0.05, it can be concluded that the application of audiovisual learning media has a significant effect on increasing students' learning interest. Therefore, audiovisual media is effectively used as an alternative learning media that can increase students' interest in learning Arts and Culture in elementary schools.